Silver‐Catalyzed Cross‐Olefination of Donor and Acceptor Diazo Compounds: Use of N‐Nosylhydrazones as Diazo Surrogate. Issue 4 (1st February 2017) - Liu, Zhaohong; Liu, Binbin; Zhao, Xue‐Feng; Wu, Yan‐Bo; Bi, Xihe
Abstract : The cross‐olefination reaction of donor and acceptor diazo compounds was explored. The use of N ‐nosylhydrazones as diazo surrogates and the dependence on silver catalysis were crucial for the reaction development. A variety of (hetero)aryl N ‐nosylhydrazones and α‐diazo esters, amides, and phosphonates were compatible, and the functionalized alkene products were afforded in good to high yields with moderate ( Z )/( E ) selectivities. The experimental and DFT calculation results suggest that the cross‐selectivity is due to selective activation of the silver catalyst for donor diazo compounds. Abstract : The cross‐olefination of donor and acceptor diazo compounds is developed by using N ‐nosylhydrazones as diazo surrogates under silver catalysis. This work, for the first time, expands the repertoire of diazo cross‐olefination to highly reactive donor diazo compounds.